Real-time Noninvasive Monitoring of Intracranial Fluid Shifts During Dialysis Using Volumetric Integral Phase-Shift Spectroscopy (VIPS): A Proof-of-Concept Study - Venkatasubba Rao, Chethan P.; Bershad, Eric M.; Calvillo, Eusebia; Maldonado, Nelson; Damani, Rahul; Mandayam, Sreedhar; Suarez, Jose I. (Neurocritical care, 2018)
Background Cerebral edema, which is associated with increased intracranial fluid, is often a complication of many acute neurological conditions. There is currently no accepted method for real-time monitoring of intracranial fluid volume at the bedside. We evaluated a novel noninvasive technique called “Volumetric Integral Phase-shift Spectroscopy (VIPS)” for detecting intracranial fluid shifts during hemodialysis. Methods Subjects receiving scheduled hemodialysis for end-stage renal disease and without a history of major neurological conditions were enrolled. VIPS monitoring was performed during hemodialysis. Serum osmolarity, electrolytes, and cognitive function with mini-mental state examination (MMSE) were assessed. Results Twenty-one monitoring sessions from 14 subjects (4 women), mean group age 50 (SD 12.6), were analyzed. The serum osmolarity decreased by a mean of 6.4 mOsm/L (SD 6.6) from pre- to post-dialysis and correlated with an increase in the VIPS edema index (E-Dex) of 9.7% (SD 12.9) (Pearson’s correlation r = 0.46, p = 0.037). Of the individual determinants of serum osmolarity, changes in serum sodium level correlated best with the VIPS edema index (Pearson’s correlation, r = 0.46, p = 0.034). MMSE scores did not change from pre- to post-dialysis. Conclusions We detected an increase in the VIPS edema index during hemodialysis that correlated with decreased serum osmolarity, mainly reflected by changes in serum sodium suggesting shifts in intracranial fluids.